2014
DOI: 10.1590/1516-635x1604437-442
|View full text |Cite
|
Sign up to set email alerts
|

Energy utilization of by-products from the soybean oil industry by broiler chickens: acidulated soapstock, lecithin, glycerol and their mixture

Abstract: Acidulated soy soapstock (ASS) and lecithin (LEC) are by-products from processing soy oil (SO) for human consumption, whereas glycerol (GLY) can be obtained through the transesterification of vegetable oils during the production of biodiesel. These are valuable by-products for poultry feeds that have been underutilized in many parts of the world. One study was conducted to estimate the AME n of ASS, LEC, GLY as well as of their mixture (MIX: 85% ASS, 5% LEC and 10% GLY). Two hundred and sixty Cobb 500 female b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 16 publications
3
11
0
1
Order By: Relevance
“…Similarly, Kim et al (2013) reported no differences in TTAR of N and EE in broilers fed diets that contained 50 g GLYC/kg but GE retention increased with GLYC supplementation. Also, Peña et al (2014) reported that the inclusion of Groesbeck et al (2008) reported that TTAR of GE and N were not affected when up to 60 g GLYC/kg was included in the diet, in agreement with the results reported herein. All this information indicates that the effects of GLYC on nutrient retention are very limited and of little practical interest.…”
Section: Total Tract Apparent Retentionsupporting
confidence: 91%
See 4 more Smart Citations
“…Similarly, Kim et al (2013) reported no differences in TTAR of N and EE in broilers fed diets that contained 50 g GLYC/kg but GE retention increased with GLYC supplementation. Also, Peña et al (2014) reported that the inclusion of Groesbeck et al (2008) reported that TTAR of GE and N were not affected when up to 60 g GLYC/kg was included in the diet, in agreement with the results reported herein. All this information indicates that the effects of GLYC on nutrient retention are very limited and of little practical interest.…”
Section: Total Tract Apparent Retentionsupporting
confidence: 91%
“…In the current research, the AME of the fats increased as the level of fat increased, probably because the ratio between the EE contained in the dietary ingredients and that of the supplemental fat was reduced (Irandoust et al, 2012). In this respect, Vieira et al (2002) and Peña et al (2014) reported in broilers that the AME of the experimental ASO source increased by 2.53 and 5.36 MJ/kg, when the level of the oil in the diet increased from 40 to 80 g/kg or from 20 to 60 g/kg, respectively. Aardsma and Parsons (2016) reported also that the TME of SO and maize oil increased by 1.01 and 2.33 MJ/kg, as the level of oil supplementation increased from 50 to 100 g/kg.…”
Section: Coefficient Of Total Tract Apparent Retention and Ame Of Thementioning
confidence: 48%
See 3 more Smart Citations